Survey Research on Quality Expectations in Interpreting: The Effect of Method of Administration on Subjects’ Response Rate - García Becerra, Olalla (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2015)
The use of new technologies within research into interpreting quality has produced new tools that are expected to increase the number of subjects taking part in survey studies. The growth of Internet users has led to a rise of online questionnaires mainly as a result of their time saving advantages. This paper compares the response rate obtained using three different ways of presenting a questionnaire about quality expectations in interpreting to subjects: in person, via an invitation to take part in an online questionnaire and by including the questionnaire within the text of an email to the subjects. The results of this study show that the subjects tend to participate more when the questionnaire is administered in person. In general male participation was higher than female, but no significant difference was observed with respect to the method of administration. Regarding the particular field of knowledge, the group of subjects working in a scientific and technological area was the only one in which the response rate for the paper “in person” questionnaire was not notably higher than for the other methods.